Field phenotyping of wheat leaf rust and stem rust - Qureshi, Naeela; Gonzalez, Blanca Minerva; Velazquez-Miranda, Hedilberto; Bhavani, Sridhar (Humana, New York, NY, 2025)
The three rust diseases, yellow (stripe) rust, black (stem) rust, and brown (leaf) rust are major challenges to wheat production, causing annual global yield losses of approximately 15 million tons valued at US$ 2.9 billion. Genetic resistance, including race-specific genes (R genes) and adult plant resistance (APR), is the primary control strategy against rust diseases. Field phenotyping plays a critical role in characterizing both types of resistance, aiding in the assessment of R and APR genes for durable resistance in breeding. Field phenotyping helps breeding programs select superior resistant germplasm by evaluating wheat lines under artificial epidemics of predominant relevant pathotypes or isolates. It allows better understanding of gene effects, interactions, stability, and responses to variable pathogen races and environments. Field phenotyping ensures rust resistance evaluations align with field circumstances and high artificial epiphytotic conditions, making breeding efforts more relevant and impactful. In conclusion, field phenotyping holds paramount importance in assessing rust resistance in wheat, providing realistic, quantitative, and environment-specific data for the development of improved wheat cultivars with enhanced rust resistance and sustainable productivity. This chapter provides a comprehensive guide to leaf and stem rust of wheat, offering a step-by-step approach to understanding these diseases and conducting field evaluations and the critical role of field phenotyping in characterizing types of resistance types. The chapter equips readers with practical insights into evaluating wheat lines under artificial epidemics, enabling researchers with the knowledge and tools necessary to contribute to breeding efforts aimed at developing improved wheat varieties with enhanced rust resistance and sustainable productivity.